Assessment of teaching and learning environment in Southwest China - Xingning Mao; Li Shao; Haiyan Yao; Hua Liang; Yuning Wei; Jie Yu; Liujuan Qin; Yanting Zhou (Medicine, 2026)
The teaching and learning environment (TLE) plays a pivotal role in medical education by influencing students’ professional development and quality of patient care. However, satisfaction levels among students varied within the TLE. This study aimed to assess TLE in medical education in southwest China. A cross-sectional study was conducted from April to May 2020 in southwest China to assess TLE among clinical medical interns across 17 hospitals, with data collected via an online questionnaire focusing on demographics, TLE perception, educational guidance, and overall satisfaction. Ordinal logistic regression was performed to identify factors that correlated with overall satisfaction. Among the 834 medical interns, 74.10% reported satisfaction with their teaching hospital, with the highest satisfaction observed in medical record writing and the lowest in living conditions. Ordinal logistic regression identified several predictors of higher satisfaction, including satisfaction with teaching rooms, teaching management staff, and medical procedures, as well as a sense of responsibility instilled by teaching preceptors and managing an average of 1 to 2 or 3 to 4 beds. Notably, attending mini-lectures at a bimonthly frequency was significantly correlated with increased satisfaction. This study highlights the importance of teaching room quality, the responsibility of teaching preceptors, medical procedures, and patient bed management, as well as the frequency of mini-lectures, as key factors influencing interns’ satisfaction. These findings provide valuable insights for medical education institutions seeking to enhance their clinical training experience and the overall satisfaction of medical interns.